Blood on the Snow : The Killing of Olof Palme - Bondeson, Jan (Book collections on Project MUSE., 2005)
"Bondeson demolishes the various conspiracy theories that have been devised to make sense of the killing, before suggesting a convincing explanation of his own. Blood on the Snow includes crime-scene photographs and reconstructions that have never before been published."--Jacket